MATHEMATICAL LITERACY’S VOCATIONAL STUDENTS BASED ON LOGICAL AND NUMERICAL REASONING - Lathifatun Ni'mah; Iwan Junaedi; Scolastika Mariani (IKIP Siliwangi and I-MES, 2017)
The research aims is (1) to obtain learning quality of CTL model to students mathematical literacy, (2) to obtain mathematical literacy description based on logical reasoning, (3) to obtain mathematical literacy description based on numerical reasoning and (4) to obtain mathematical literacy description based on logical and numerical reasoning. The research type is descriptive study. The subject is XI AK SMK NU Lasem were taken 6 students high, medium and low logical reasoning, 6 students high, medium, and low numerical reasoning, 6 students high, medium, and low logical and numerical reasoning, 2 students high logical and medium numerical reasoning, 2 students medium logical and high numerical reasoning. The research result is (1) CTL models learning quality for mathematical literacy is good, (2) student mathematical literacy based on high logical reasoning level 4 and 5, medium level 3, low level 1 and 2, (3) student mathematical literacy based on high numerical reasoning level 5, medium level 4, low level 2 and 3, (4) student mathematical literacy based on high logical and numerical reasoning level 5, medium level 3 and 4, high logical and medium numerical reasoning or medium logical and high numerical reasoning level 4 and 5, low level 1 and 2.